Experimental Study on Mechanical Properties of Gas Storage Sandstone under Water Content - Sinan Zhu; Junchang Sun; Yingjie Wu; Baoyun Zhao; Li Zhang; Xin Zhang; Bingyuan Wang (Advances in Civil Engineering)
In order to investigate the influence of water content on the damage and degradation characteristics of Hutubi sandstone, different saturation experiments and laboratory mechanical experiments were carried out on Hutubi sandstone. The experimental results show that under uniaxial and triaxial conditions, with the increase in water content, the axial, lateral, and volume deformations gradually increase, and the deformation shows obvious dilatancy characteristics. The deviator stress and elasticity modulus of the sandstone decreased exponentially with the increasing water content. Confining pressure has a significant effect on the strength improvement of sandstone under the constant water content. Based on lognormal distribution, the damage constitutive model of sandstone which can reflect both uniaxial and triaxial condition with different water contents was proposed. The theoretical curves were compared with the experimental curves, and it was found that the theoretical curves and the experimental curves have similar changing trends. It shows the rationality of the statistical damage constitutive model.